Flexing in the lens of Christian education: Children's failure to stem the negative influence of the era of disruption or neglect of parents instilling early childhood character - Simatupang, Ronny; Imeldawati, Tiur; Ariawan, Sandy; Widiastuti, Maria (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2022)
Flexing becomes a phenomenon that threatens the morality of the younger generation of Christians in this disruption era. The question that then arises is, this is just a common phenomenon, or is it the form of failure of Christian parents to shape the child's personality? In Christian education in the family sphere, learning is emphasized on developing the potential of spiritual intelli-gence (psychiatric or spiritual and inner). The family is the right place for the growth of awareness of the beginning of the purpose and existence of life. It is the responsibility of the family to ensure that a child develops and grows into a good adult human being and can take care of himself, and not depend on others. The formation of personality at an early age is something that must be fulfilled and cannot be delayed. It is said that approximately 85% of basic human personalities are formed at the age of 0-6 years, and the rest are just polishing. This study aims to prove how much influence character cultivation by parents has on the potential flexing in children. The approach used in this study is quantitative, with a sample of 100 children. The results of data collection are analyzed using simple linear regression with the help of SPSS 23.0. The results of the study proved that the cultivation of personality by parents affected the flexing potential of children by 69%, while 31% was influenced by other factors. Further findings in this study, the formation of behavior in a planned, systematic, and targeted manner was shown to be able to reduce the potential for flexing by 73% in children. As a contribution to this study, it is recommended to parents instill humility, meek, patience, love, and peace in children from an early age. This has been shown to be able to ward off flexing which is a negative effect of the disruption era.